1999
DOI: 10.1007/bf03343583
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of acromegaly with the somatostatin analogue SR-lanreotide

Abstract: Long-term treatment of acromegaly with SR-lanreotide is effective in controlling GH and IGF-I levels and symptoms and is well tolerated in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 26 publications
4
26
0
3
Order By: Relevance
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other trials with lanreotide SR (16,22,25), we observed a small rise in fasting blood glucose during therapy, whereas others found no change in glucose metabolism (23). In our study, as well as in others (22,23), no obvious deterioration in glucose metabolism was seen in patients with overt diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from octreotide sensitivity, response to treatment was not in¯uenced by sex, previous surgery nor previous radiotherapy, similar to the experience in other studies (25). Patients whose GH or IGF-I levels were not normalized tended to have higher pre-treatment levels, but the difference was not signi®cant.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, Bevan (37) estimated that, of 921 cases included in the analysis, 20 -or 2.2% -had tumor growth on somatostatin analogs (37). Failure to control pituitary adenoma growth occurred in approximately 10% in individual studies using lanreotide (38,39) and octreotide (40), which were not included in that analysis. Another issue that may confound accurate analysis of tumor behavior in general is the fluctuation in tumor size to the order of 10 -20%, which can be seen during intensive MRI follow-up in individual acromegalic patients treated with somatostatin analogs (33).…”
Section: Medical Therapymentioning
confidence: 99%
“…Such biomarkers include the acute octreotide test, the presence of a gsp mutation, the expression of E-cadherin, the expression of sst5 and its truncated isoform (sst5TMD4), the expression of miR-34a, the expression of β-arrestin, the Ki-67 labeling index and the Raf kinase expression 57,68,72,83,[86][87][88][89][90][91] . Additionally, some demographic characteristics, such as younger age, male gender and high pretreatment GH levels were associated with a poor response to fg-SRL in some studies [92][93][94] .…”
Section: Biomarkers Of Treatment Response In Acromegalymentioning
confidence: 99%